Married rural women's working status and their participation in household decision-making. - Claur, Ave C
This study was undertaken to identify the areas of household decision-making were married women actively participate. The variable being used in this study is their working status. Thus, it seeks to find out if there is a relationship between married women's working status and their participation in household-making. This study also seeks to find out whether financial-economic areas of decision-making are wife-dominated area and whether socio-moral related area is also wife-dominated area of decision-making. The primary instrument used to gather data was the interview schedule. This study was conducted in Brgy. Pungtod Cabatuan. The researchers used the Yamane's formula in determining the sample size. The chi-square test was also used to determine the relationship between the variables. More so, frequency and percentage counts were employed to make results comprehensible. The study found that married women whether they are working or not participate in two areas of household decision-making. Chi-square results shows that working status of married women has no significant effect on their participation in making decisions in the family. That they are involved in every aspect of family decisions.